RELIGIOUS FREEDOM IN INDONESIA: Between Upholding Constitutional Provisions and Complying with Social Considerations - Maula, Bani Syarif (JOURNAL OF INDONESIAN ISLAM, 2013)
Human rights, including freedom of religion, are generally accepted and granted by all governments regardless of their ideology, political, economic, and social conditions. In a Muslim majority country such as Indonesia, ideally freedom of religion is considered to mean that the government allows religious practices of religious minorities or other sects besides the state religion, and does not persecute believers in other faiths. This paper discusses Indonesiaâs constitutional provisions concerning legal rights of citizens on freedom of religion, whether the government upholds the constitution as a concrete way to deal with human rights protection or it complies with some groupsâ demand to tighten restrictions on âthe Western concept ofâ religious liberty. This paper concludes that even though there are many provisions in the Indonesiaâs constitution and in its legal system which is supportive of religious freedom, some governmental provisions were enacted based on social considerations, rather than to strengthen constitutional provisions.